Prostaglandins, leukotrienes, and other eicosanoids: from biogenesis to clinical application - Marks, Friedrich; Fürstenberger, Gerhard (Wiley-VCH, 1999)
Arachidonic acid and companions : an abundant source of biological signals / Friedrich Marks -- The generation of free arachidonic acid / Peter Dieter -- Cyclooxygenases / Karin Müller-Decker -- Prostanoid synthases / Christian Martin and Volker Ullrich -- Lipoxygenases / Hartmut Kühn -- Oxygenation of arachidonic Acid by cytochromes P-450 / Ernst H. Oliw and Johanna Ericsson -- Renal eicosanoids / Margarete Goppelt-Strübe and Joachim Fauler -- The role of eicosanoids in reproduction / H.P. Zahradnik, B. Wetzka and W.R. Schäfer -- The role of eicosanoids in inflammation and allergy / Eva Wikström Jonsson and Sven-Erik Dahlén -- Prostanoids in the cardiovascular system / Lukasz Partyka, Arsineh Arakil Aghajanian and Helmut Sinzinger -- Eicosanoids and cancer / Friedrich Marks and Gerhard Fürstenberger -- Synthetic eicosanoids : development and clinical applications / Bernd Buchmann [and others].